NEAr Transporter (NEAT) Domains: Unique Surface Displayed Heme Chaperones That Enable Gram-Positive Bacteria to Capture Heme-Iron From Hemoglobin - Ellis-Guardiola, Ken; Mahoney, Brendan J.; Clubb, Robert T. (Frontiers in Microbiology, 2021)
Many bacterial pathogens forage iron from human hemoglobin (Hb) because it contains vast quantities of this precious metal in the form of heme (iron–protoporphyrin IX). Several clinically important pathogenic species within the Firmicutes phylum scavenge heme using surface-displayed or secreted NEAr Transporter (NEAT) domains. In this review, we discuss how these versatile proteins function in the Staphylococcus aureus Iron-regulated surface determinant system that scavenges heme-iron from Hb. S. aureus NEAT domains function as either Hb receptors or as heme-binding chaperones. Heme-binding NEAT domains rapidly exchange heme amongst one another via transiently-forming transfer complexes, suggesting that they form a protein-wire within the peptidoglycan through which heme flows from the microbial surface to the membrane. In Hb receptors, recent studies have revealed how dedicated heme- and Hb-binding NEAT domains function synergistically to extract Hb’s heme molecules, and how receptor binding to the Hb-haptoglobin complex may prolong microbial access to Hb’s iron. The functions of NEAT domains in other Gram-positive bacteria are also reviewed.